Seroprevalence and Risk Factors of Toxoplasma gondii Infection among Domestic Ruminants in East Hararghe Zone of Oromia Region, Ethiopia - Berhanu Tilahun; Yacob Hailu Tolossa; Getachew Tilahun; Hagos Ashenafi; Shihun Shimelis (Veterinary Medicine International)
A cross-sectional study was carried out from July 2011 to September 2013 to assess the seroprevalence and identify risk factors of Toxoplasma gondii infection in domestic ruminants of East Hararghe zone of Oromia region, Ethiopia. Sera of 1360 domestic ruminants were analyzed for the presence of anti-T. gondii IgG antibodies using the indirect enzyme-linked immunosorbent assay (iELISA). Additionally, the owners were also interviewed using a structured questionnaire to identify the potential risk factors of T. gondii infection. Overall, the prevalence of T. gondii infection in domestic ruminants was 22.2% (302/1360). The seroprevalence in sheep, goats, cattle, and camels was 33.7%, 27.6%, 10.7%, and 14.4%, respectively. District, species, sex, age, and water source were identified as risk factors for T. gondii infection. Increased seropositivity was observed in females (OR = 2.63) and also with the use of pond (OR = 4.25) and pipe (OR = 9.57) water sources in sheep; age >1 year old (OR = 3.45) and with drinking from pond (OR = 6.03) and pipe (OR = 11.61) water sources in goats; with the use of pond (OR = 5.60) and pipe (OR = 10.68) water sources in cattle; and in >4-year-old camels (OR = 2.49). In conclusion, T. gondii infection is common and widespread among the domestic ruminants of the study area, indicating the potential transmission to humans from these animals when they are used as a source of food. Hence, it is crucial to raise awareness of the people about T. gondii infection and conduct further study to explore the impact of the disease on food animal production.